PERENCANAAN, IMPLEMENTASI, DAN TANTANGAN PENGEMBANGAN KETERAMPILAN SOSIAL SISWA SD MELALUI MODEL PEMBELAJARAN KOOPERATIF (STUDI LITERATUR) - Agustina Yulianti; Taufik Muhtarom (STKIP Subang, 2026)
This study aims to analyze the planning, implementation, and challenges of developing elementary school students' social skills through the cooperative learning model. This research method uses a literature study method by reviewing 30 relevant journal articles published between 2020-2026. The data collection technique is through the Google Scholar database using specific keywords. The process of selecting articles goes through the stages of inclusion and exclusion. Including (1) the researcher entered the keyword